Rapid popliteal artery release sensu A.N. Kazantsev in acute thrombosis in patients with COVID-19 - A. N. Kazantsev; K. P. Chernykh; G. Sh. Bagdavadze; N. E. Zarkua; E. Yu. Kalinin; S. V. Artyukhov; A. E. Chikin; Yu. P. Linets (Российский кардиологический журнал)
Aim. To analyze the outcomes of popliteal thrombectomy using the standard release technique with vascular instruments and rapid release sensu A. N. Kazantsev in patients with acute popliteal artery thrombosis (PAT) and coronavirus disease 2019 (COVID-19).Material and methods. The present prospective single-center study for the period from April 1, 2020 to March 17, 2021 included 157 patients with acute PAT and COVID-19 at the Alexandrovskaya City Hospital. All patients were divided into 2 groups depending on the popliteal artery access: group 1 (n=88; 56%) — rapid release sensu A. N. Kazantsev; group 2 (n=69; 44%) — standard popliteal artery release using vascular instruments (vascular forceps and scissors) and tourniquets. Rapid popliteal artery release was distinguished by the fact that fasciotomy and hemostasis, the fatty tissue behind it and up to the artery was torn with two index fingers. First, the fingers were joined together at the lateral edges and inserted into the wound middle. Then the wound together with tissues was stretched with fingers to proximal and distal edges until the popliteal artery was visualized. Further, a Beckmann retractor was used to fix the torn fiber to the upper and lower wound walls. The tourniquets were not used.Results. Surgical access duration (group 1, 4,5±1,3 minutes; group 2, 11,41±0,9 minutes; p=0,005), as well as the total procedure duration (group 1, 47,5±2,8 minutes; group 2, 62,15±4,5 min; p=0,001) had the lowest values in the group of rapid popliteal artery release. Moreover, all intraoperative bleedings (n=11; 15,9%) was recorded in group 2 as a result of popliteal vein injuries and/or bleeding from popliteal artery. The retrombosis rate in the rapid release group was lower (group 1, 40,9%; group 2, 55,1%; p=0,03). On the first day after surgery, 18% of thrombosis developed in group 1, and 39% in group 2. The mortality rate was highest in the standard artery release group (group 1, 55,7%; group 2, 86,9%; p<0,0001; OR, 0,18; 95% CI, 0,08-0,42). In all cases, the cause of death was systemic multiple organ failure due to severe pneumonia, pulmonary edema, and cytokine storm.Conclusion. The use of rapid popliteal artery release sensu A. N. Kazantsev significantly reduces the thrombectomy duration in the context of COVID-19. This effect is achieved due to a decrease in the incidence of intraoperative bleeding, no need to use tourniquets and vascular instruments. A decrease in the ischemia duration using novel release technique reduces the retrombosis rate, as well as deaths caused by systemic multiple organ failure against the background of hyperperfusion and compartment syndrome. Reducing the operation duration with the use of rapid popliteal artery release sensu A. N. Kazantsev reduces the time of intraoperative mechanical ventilation, which in COVID-19 patients reduces the risks of pneumothorax, pneumomediastinum, emphysema, and pulmonary embolism. Thus, the rapid popliteal artery release sensu A. N. Kazantsev can be recommended for popliteal thrombectomy in patients with COVID-19.